2011
DOI: 10.7732/kjpr.2011.24.6.696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mepiquat Chloride and Trinexapac-Ethyl on Oil Composition, Seed Yield and Endogenous Gibberellins in Flax

Abstract: -The aim of this field experiment was to investigate the possible effects of mepiquat chloride (TE) and trinexapac-ethyl (MC) on oil composition, seed yield and endogenous gibberellins content of flax cultivar. Foliar application of plant growth retardants mepiquat chloride (0.897, 1.794 and 2.691 kg a.i. ha -1 ) and trinexapac-ethyl (0.756, 1.512 and 2.668 kg a.i. ha -1 ) had significantly increased seeds ripening rate and seed yield. In contrast, plant height was decreased by foliar application of MC and TE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…The combination treatment of lower MC and elevated TE (treatment T2, T3, T4) was found to have a significant effect over control compared to the higher MC and elevated TE (treatment T5, T6, T7). In a previous study, we reported that single MC treatment had a higher seed ripening than TE treatment (Kim et al, 2011). In this study, however, combined treatment of MC with TE gave a lower seed ripening rate than that of single MC treatment.…”
Section: Growth Attributesmentioning
confidence: 48%
See 3 more Smart Citations
“…The combination treatment of lower MC and elevated TE (treatment T2, T3, T4) was found to have a significant effect over control compared to the higher MC and elevated TE (treatment T5, T6, T7). In a previous study, we reported that single MC treatment had a higher seed ripening than TE treatment (Kim et al, 2011). In this study, however, combined treatment of MC with TE gave a lower seed ripening rate than that of single MC treatment.…”
Section: Growth Attributesmentioning
confidence: 48%
“…Farooqi and Sharma (1988) reported that plant growth retardant such as chlormequat chloride increased significantly oil contents and inhibited growth in Japanese mint. Kim et al (2011) reported that the foliar spray of single treatment with MC caused higher oil content than that of TE.…”
Section: Content Of Oil and Lignan And Fatty Acid Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have focused on changes of endogenous gibberellins to get a better understanding together with better agronomic practices. In a previous study, it was revealed that foliar application of mepiquat chloride increases seed oil content and promotes unsaturated fatty acids in flax (Kim et al, 2011). The present study aimed to evaluate the optimal concentration of plant growth retardants in order to increase seed yield and oil content in flax plants.…”
Section: Introductionmentioning
confidence: 91%